Comparison of lead dioxide and cerium dioxide as mediators for carbon paste electrodes in flow injection-amperometric detection of hydrogen peroxide - Mihić-Necin, Bojana; Guzsvány, Valéria; Kalcher, Kurt (Univerzita Pardubice, 2010)
Carbon paste electrodes (graphite / paraffin oil), bulk-modified with lead dioxide and cerium dioxide, were used as sensors for the amperometric determination of hydrogen peroxide in flow injection analysis. Experimental parameters, such as applied working potential, flow rate of the carrier and injection volume were optimized with a thin-layer flow-through cell. The method was validated with respect to calibration curve, linear dynamic range, detection limit, repeatability and reproducibility.
Keywords: cerium dioxide; lead dioxide; mediators; FIA; hydrogen peroxide